STEM Carnival with SMK Ayer Puteh - UMP, PNC (2018)
Kemaman, 19 September – Nearly 300 students from Sekolah Menengah Kebangsaan Ayer Puteh Kemaman participated in Science, Technology, Engineering and Mathematic (STEM) Carnival, held in conjunction with APSES Co-curricular Day school level. Programme was facilitated by 10 undergraduates from Scitexs Club from Faculty of Industrial Science and was jointly organized by School Co-curricular, Library TV Unit and Department of Language.